Corticosteroid Dosing in Pediatric Acute Severe Ulcerative Colitis: A Propensity Score Analysis. Issue 1 (July 2016) - Choshen, Sapir; Finnamore, Helen; Auth, Marcus K.H.; Bdolah-Abram, Tali; Shteyer, Eyal; Mack, David; Hyams, Jeffrey; Leleiko, Neal; Griffiths, Anne; Turner, Dan
ABSTRACT: Objectives: We aimed to explore the optimal dosing of intravenous-corticosteroids (IVCS) using a robust statistical method on the largest pediatric cohort of acute severe colitis to date. Methods: Two hundred eighty-three children treated with IVCS for ulcerative colitis were included and studied for 1 year (46% boys, age 12.1 ± 3.9 years, disease duration 2 (interquartile range [IQR] 0–14) months, baseline Pediatric Ulcerative Colitis Activity Index 69 ± 13 points). Confounding by indication was addressed by matching high- and low-IVCS dose patients according to the propensity score method, using 3 cutoffs (1 mg · kg −1 · methylprednisolone to 40 mg · day −1, 1.25 mg · kg −1 to 50 mg · day −1 and 2 mg · kg −1 to 80 mg · day −1 ). Results: The median IVCS dose in the entire cohort was 1.0 mg · kg −1 · day −1 (IQR 0.8–1.4) and 44 mg · kg −1 · day −1 (32–60). Ninety-four of 283 children were matched in the low-dose cutoff (1 mg · kg −1 · day −1 ), 218 of 283 were matched in the middle cutoff (1.25 mg · kg −1 · day −1 ), and 86/283 in the high dose cutoff (2 mg · kg −1 · day −1 ). No differences were found in 25 pretreatment baseline variables in the three cutoffs, implying successful matching. There were no statistical differences in the outcomes of the two lower cutoffs (including need for salvage therapy during admission and by 1 years, admission duration, and day-5 Pediatric Ulcerative Colitis Activity Index<35 points; all P > 0.05). In the high cutoff, the higher doses were somewhat better but this benefit reversed in a sensitivity analysis excluding one center. High doses were not associated with better outcome also in a propensity score-weighted regression model on the entire cohort. Conclusions: Our data support present guidelines that doses of IVCS >1 to 1.5 mg · kg −1 · day −1 (maximum 40–60 mg · kg −1 · day −1 ) are not justified in acute severe colitis.